Hubungan Antara Tingkat Insomnia Dengan Konsentrasi Belajar Pada Mahasiswa Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung - Alif Ansyari Anzar; Moch Aspihan; Iskim Luthfa (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Insomnia is a sleep disorder characterized by difficulty initiating or maintaining sleep and is commonly experienced by nursing students who face substantial academic demands. This condition has the potential to increase academic stress, reduce concentration, and impair cognitive functions such as memory and critical thinking, thereby diminishing the effectiveness of the learning process. This study aimed to examine the relationship between insomnia severity and learning concentration among nursing students. A quantitative approach with a cross-sectional design was employed. The study population comprised 316 undergraduate nursing students at Sultan Agung Islamic University, with 177 respondents selected through stratified random sampling. Data were collected using the KSPBJ-IRS instrument to measure insomnia severity and a learning concentration questionnaire adapted from previous research. Data analysis was performed using SPSS version 25 and Somers’ d correlation test. The results indicated a statistically significant relationship between insomnia severity and learning concentration, with a negative correlation direction. The correlation coefficient was -0.502 with a p-value of 0.000. These findings suggest that higher levels of insomnia are associated with lower learning concentration among students. This study concludes that there is a significant negative relationship between insomnia severity and learning concentration. The findings are expected to serve as a foundation for educational institutions in developing effective promotive interventions.